Assessing a decade of regulatory performance for the Lesotho electricity industry. (August 2015) - Thamae, Leboli Z.; Thamae, Retselisitsoe I.; Thamae, Thimothy M.
Abstract: Government-run electricity utilities around the world have been subjected to reform and regulation over the last two decades in an effort to introduce private investment and competition for reliable and affordable services in support of socio-economic development. Although extensive scholarly literature abounds with regard to experiences with restructuring and regulation in many developed economies, research on electricity-sector regulatory performance in small African developing countries like Lesotho is still rare. This article provides an empirical assessment of the three critical regulatory dimensions of governance, substance, and impact in order to evaluate the performance of electricity industry regulation in Lesotho for the period 2004–2014. Highlights: Lesotho has established good governance for an independent regulator but improvements in substance are still required. Satisfactory regulatory impact in terms of household access, predictable tariff setting and utility's efficiency has been recorded. However, attracting new generation investment, attaining full compliance and cost-reflectivity pose an immediate challenge.